2018
DOI: 10.1111/ap.12288
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pathological Worry in Children With Acceptance‐Based Behavioural Therapy and a Multisensory Learning Aide: A Pilot Study

Abstract: Objective The primary objective of this study was to provide an initial test of the efficacy of acceptance‐based behavioural therapy in reducing pathological worry and anxious symptomology in children. A secondary objective was to examine the benefit of supplementing standard acceptance‐based behavioural therapy with a multisensory learning aide (MSA). The MSA provides kinaesthetic, tactile, and visual stimuli to facilitate children's understanding of acceptance‐based behavioural therapy principles and the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
(118 reference statements)
0
8
0
Order By: Relevance
“…Single Case Design Gauntlett-Gilbert, Connell, Clinch, and McCracken (2013) No standardized parent outcome measure used Goodarzi, Soltani, Seddigh, Hamdami, and Jobaneh (2017) Study not in English Hadlandsmyth, White, Nesin, and Greco (2013) Theoretical paper Hayes et al (2011) Parents not involved in treatment Makki et al (2018) Parents not involved in treatment Masuda, Cohen, Wicksell, Kemani, and Johnson (2011) Single case design Merwin, Zucker, and Timko (2013) No inferential statistics used Meagher, Chessor, and Fogliati (2018) Intervention not ACT Moghanloo, Moghanloo,and Moazezi (2015) Parents not involved in treatment Petts, Duenas, and Gaynor (2017) Parents not involved in treatment Reid, Gill, Gore, and Brady (2016) Qualitative study Samani, Sajjadian, and Shadehee (2016) Study not available in English Szabo, Willis, and Palinski (2019) No parent report outcome Thurstone, Hull, Timmerman, and Emrick (2017) Parents not involved in treatment Wicksell, Melin, and Olsson (2017) No standardized parent outcome measure used Wicksell, Dahl, Magnusson, and Olsson (2005) No standardized parent outcome measure used Woidneck, Morrison, and Twohig (2014) Parents not involved in treatment…”
Section: Fundingmentioning
confidence: 99%
“…Single Case Design Gauntlett-Gilbert, Connell, Clinch, and McCracken (2013) No standardized parent outcome measure used Goodarzi, Soltani, Seddigh, Hamdami, and Jobaneh (2017) Study not in English Hadlandsmyth, White, Nesin, and Greco (2013) Theoretical paper Hayes et al (2011) Parents not involved in treatment Makki et al (2018) Parents not involved in treatment Masuda, Cohen, Wicksell, Kemani, and Johnson (2011) Single case design Merwin, Zucker, and Timko (2013) No inferential statistics used Meagher, Chessor, and Fogliati (2018) Intervention not ACT Moghanloo, Moghanloo,and Moazezi (2015) Parents not involved in treatment Petts, Duenas, and Gaynor (2017) Parents not involved in treatment Reid, Gill, Gore, and Brady (2016) Qualitative study Samani, Sajjadian, and Shadehee (2016) Study not available in English Szabo, Willis, and Palinski (2019) No parent report outcome Thurstone, Hull, Timmerman, and Emrick (2017) Parents not involved in treatment Wicksell, Melin, and Olsson (2017) No standardized parent outcome measure used Wicksell, Dahl, Magnusson, and Olsson (2005) No standardized parent outcome measure used Woidneck, Morrison, and Twohig (2014) Parents not involved in treatment…”
Section: Fundingmentioning
confidence: 99%
“…Recent reviews have reported that mindful-based interventions (MBI) are feasible for young participants [1]. MBI for children and adolescents are promising initiatives, as there is evidence of their usefulness in treating childhood anxiety [2], reducing symptoms of obsessive-compulsive disorder [3], and their pathological concerns [4].…”
Section: Introductionmentioning
confidence: 99%
“…Three studies used an RCT design to compare ACT with another active treatment (Hancock et al, 2018;Meagher, Chessor & Fogliati, 2018;Swain et al, 2015b). Hancock et al (2018) and Swain et al (2015b) used block randomisation to compare ACT with a CBT intervention as well as a waiting list control, and Meagher et al (2018) randomised participants on an individual basis to compare Acceptance-Based Behaviour Therapy with Acceptance-Based Behaviour Therapy in conjunction with a multisensory learning aide. Four studies used an RCT design to compare ACT to a non-active control group (Buckhardt et al, 2016(Buckhardt et al, , 2017Lee et al, 2018;Van der Gucht et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…using a number of research sites, including young people of different ethnicities and socioeconomic status). Six studies used samples which were moderately or completely representative of the target population, whereas two were slightly representative (Buckhardt et al, 2017;Timko et al, 2015) and two were not representative (or did not provide information about the target group) (Barney, Field, Morrison, & Twohig, 2017;Meagher et al, 2018). Few studies provided detailed descriptions of the data collection procedure, with four studies providing a complete description (Barney et al, 2017;Buckhardt et al, 2017;Hancock et al, 2018;Van der Gucht et al, 2017).…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%